2017
DOI: 10.1111/jai.13565
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of paddlefish (Polyodon spathulaWalbaum, 1792) spawning habitat availability with consumer-grade sonar

Abstract: Summary The paddlefish (Polyodon spathula Walbaum, 1792) is a springtime migrant that requires discrete abiotic conditions such as water temperature, discharge, and substrate composition for successful spawning and recruitment. Although population declines have prevailed throughout much of the species range, Oklahoma paddlefish are abundant and support popular recreational snag fisheries – most notably in Grand Lake. This stock utilizes the Grand Lake's two primary headwaters, the Neosho and Spring rivers, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…The resulting river bottom hardness values exhibited little variance and the value was high (hard category: 0.4-0.5) at most of the measuring points. Previous studies conducted in lakes have shown a wider range of EcoSound hardness values and the output has been successfully used to determine different bottom types [36,39,40]. The softest values were recorded on "muck", mud, and silt [39,40], which were mostly missing on our study area.…”
Section: Bottom Hardnessmentioning
confidence: 74%
See 2 more Smart Citations
“…The resulting river bottom hardness values exhibited little variance and the value was high (hard category: 0.4-0.5) at most of the measuring points. Previous studies conducted in lakes have shown a wider range of EcoSound hardness values and the output has been successfully used to determine different bottom types [36,39,40]. The softest values were recorded on "muck", mud, and silt [39,40], which were mostly missing on our study area.…”
Section: Bottom Hardnessmentioning
confidence: 74%
“…Previous studies conducted in lakes have shown a wider range of EcoSound hardness values and the output has been successfully used to determine different bottom types [36,39,40]. The softest values were recorded on "muck", mud, and silt [39,40], which were mostly missing on our study area. Most of the silt/clay bottoms in our study area were located in the near-shore areas where depth was preventive of the use of the EcoSound method, and therefore the amount of data collected was lower in that substrate size class.…”
Section: Bottom Hardnessmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, Oologah Lake on the Verdigris River was stocked from 1995 to 2000 and has since shown signs of natural recruitment, whereas Lake Texoma on the Red River (outside our study area) was stocked from 1997 to 2007 but has not evidenced natural recruitment (Patterson, , J. Schooley, ODWC, personal communication). The exact mechanisms behind this variation in restoration success remain unknown, but the hydrology and availability of suitable spawning habitat in upstream tributaries is considered key (Patterson, ; Paukert & Fisher, ; Schooley & Neely, ). Our ensemble map provided a visualization of stream reaches that were estimated as suitable for paddlefish.…”
Section: Discussionmentioning
confidence: 99%
“…Effective management of paddlefish (Polyodon spathula), an ancient river-spawning species native to the central United States (Gengerke 1986;Bettoli, Kerns, and Scholten 2009), is predicated on understanding the reproduction and patterns of movements of this highly mobile, migratory species (Russell 1986;Jennings and Zigler 2000;Scarnecchia et al 2007). Many aspects of the species' upriver spawning migrations and reproductive success are influenced by interannual variations in riverine habitat quantity and quality (Braaten, Fuller, and Lott 2009;Schooley and Neely 2018;Tripp, Neely, and Hoxmeier 2019). Interannual variations in river conditions also influence less directed, non-spawning movements of stocks (Southall and Hubert 1984;Moen, Scarnecchia, and Ramsey 1992;Tripp, Neely, and Hoxmeier 2019).…”
Section: Introductionmentioning
confidence: 99%